Afghnistan - Hamilton, Angus (J. B. Millet Co., 1910)
This book introduce about the orenburg - Tashkent railway, the Khanate of Bokhara, the province of Samarkand, the district of Merv, from Tashkent to Merv, the northern border, the murghab valley railway...